2011
DOI: 10.1002/sce.20434
|View full text |Cite
|
Sign up to set email alerts
|

Sources of efficacy information in an inservice program for elementary teachers

Abstract: Low teacher self‐efficacy is an important factor constraining the teaching of science at the elementary level. This study was designed to investigate the effectiveness of particular sources of efficacy information for enhancing the science teaching self‐efficacy of practicing elementary teachers. Twelve teachers participated in an intervention that was designed to provide them with cognitive mastery, enactive mastery, modeling, and verbal persuasion. Data were collected prior to, during, immediately after, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 63 publications
3
75
0
6
Order By: Relevance
“…Teachers better understanding of pedagogical concepts also serves to deepen mastery experiences (Palmer, 2011) which, Bandura (1997 notes is the most important source for raised self-efficacy. Hence, the findings support Palmer's concept that to fully enhance self-efficacy, mastery experiences are not only accessed through teaching the activities (enactive mastery) but also through understanding the theories of the pedagogical strategy chosen (cognitive mastery).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers better understanding of pedagogical concepts also serves to deepen mastery experiences (Palmer, 2011) which, Bandura (1997 notes is the most important source for raised self-efficacy. Hence, the findings support Palmer's concept that to fully enhance self-efficacy, mastery experiences are not only accessed through teaching the activities (enactive mastery) but also through understanding the theories of the pedagogical strategy chosen (cognitive mastery).…”
Section: Discussionmentioning
confidence: 99%
“…Mastery experiences have been consistently identified as the most influential source of self-efficacy (for example, Bandura, 1997). Going further, Palmer (2006Palmer ( , 2011 proposed that teachers could access mastery experiences through both teaching the activities, that is enactive mastery, and through understanding the theories underpinning the programme, that is cognitive mastery. As this study took place during a professional development programme, it was important to establish an awareness of how the sources and strategies might influence teachers' beliefs and self-efficacy.…”
Section: Self-efficacy and Pedagogymentioning
confidence: 99%
See 1 more Smart Citation
“…Our research centred on exploring the extent to which teachers make sense of and thereafter operationalise the concept of science capital in their teaching. In other words we sought to examine the teachers' acquisition of both cognitive and enactive mastery (Palmer, 2011) with respect to science capital. We framed our investigation around two questions:…”
Section: The Studymentioning
confidence: 99%
“…While some studies have found that teachers with high efficacy for science teaching have a strong background in science content and use more child centred teaching strategies (deLaat & Watters, 1995) and that professional development aimed at increasing teachers' science content knowledge has a positive impact on efficacy (Swackhamer, Koellner, Basile & Kimbrough, 2009), efficacy for teaching primary science is still not completely understood. Despite research in this field spanning twenty years, Palmer (2011) contends that lack of efficacy for teaching science is "still very much alive" (p. 2).…”
Section: Introductionmentioning
confidence: 99%